A Search for Large‐Scale Variations in the Fine‐Scale Structure of Earth's Inner Core. Issue 9 (7th September 2022) - Wu, Sin‐Mei; Pang, Guanning; Koper, Keith D.; Euler, Garrett
Abstract: A hemispherical pattern in inner core attenuation ( Q ) has been observed from the apparent Q of inner core transmitted waves ( PKP DF ). How the elastic scattering ( Q SC ) originating from kilometer‐scale inner core heterogeneities relates to large‐scale apparent Q variations remains elusive. Such inner core scattered (ICS) energy is characterized by emergent, long‐lasting, high‐frequency (1–4 Hz) coda immediately following pre‐critical reflections ( PKiKP ) from the inner core boundary (ICB). In this study, we develop a framework to systematically investigate ICS and examine its hemispherical pattern using data from two arrays that sample opposing sides of the Pacific quasi‐hemispherical boundary. We use all the viable data from earthquakes ( M w  ≥ 5.8) within the past 2–3 decades recorded at distances of 50°–75° by YKA and ILAR—small‐aperture (∼10–20 km) seismic arrays situated in northwestern North America. Two independent waveform stripping methods are applied to extract ICS from the background energy, and various stacks are performed to identify ICS and its spatial pattern. We found that individual beams lacking clear evidence of PKiKP coda waves reveal ICS characteristics when stacked together, implying that ICS is ubiquitous. We used a modified phonon‐based simulation to reinforce the idea that ICS is primarily created by volumetric heterogeneity within the inner core as opposed to ICB topography. With simplified two‐layer ICS models, our results suggest that ICS within the eastern quasi‐hemisphere is slightly stronger than in the western quasi‐hemisphere, although intra‐hemispherical variations are as significant, and our sampling is limited to patches of the northern hemisphere. Plain Language Summary: The Earth's inner core is well known to be seismically heterogeneous at scales of 1–10 km. However, the regional variation in inner core heterogeneity and its relationship to the well‐known inner core hemispherical dichotomy are poorly understood. The fine‐scale heterogeneity is manifested in high‐frequency (1–4 Hz) scattered energy following reflections from the inner core boundary and is very difficult to observe. Here, we present a new framework to systematically investigate the fine‐scale structure of Earth's inner core using earthquake data recorded by two small‐aperture seismic arrays of the International Monitoring System. Our data and resulting models suggest that the inner core heterogeneity structure has significant regional variations and is slightly weaker within the western hemisphere. We also find that the heterogeneity strength changes with depth in the inner core. Our results provide new clues to understanding the evolution of Earth's core. Key Points: PKiKP coda waves recorded by seismic arrays at distances of 50°–75° are used to observe and model inner core scattered energy Significant scattering is observed on both sides of the Pacific quasi‐hemispherical inner core boundary at northern latitudes Variations in scattering strength are observed between and within the quasi‐hemispheres